Improving Employee Performance Measurement: An Approach for Designing New Features in the New-Siransija Application - Rahmat Taufik R.L Bau; Hermila A.; Hilal Bouti (International Journal of Computer and Information System (IJCIS), 2023)
This study presents the design and development of new features in the New-Siransija application using an object-oriented system approach. The main objective is to optimize employee performance measurement and improve personnel administration within the Gorontalo Provincial Government. This study uses a qualitative methodology, adapting the first three stages of the Software Development Life Cycle (SDLC). The weakness identified in the current system lies in the assignment feature input section. To overcome this, this study proposes the integration of the upload feature for assignment documentation, which is linked to the payroll recording system. These enhancements aim to prevent potential abuse and increase accountability by requiring employees to provide proof of completed assignments. The development process involves a qualitative analysis of user needs and system requirements, followed by the design and implementation of new features. The results of the study show that the features designed in the New-Siransija application which were developed through an object-oriented system approach improve employee performance measurement and encourage accountability within the Gorontalo Provincial Government.